Penerapan Metode TOPSIS Untuk Menentukan Penerima Bantuan Santri Kurang Mampu Pada Lembaga Pendidikan Islam Pondok Pesantren - Qoif Sahroni; Derman Janner Lubis (Universitas Binaniaga Indonesia, 2023)
In The educational unit is one of the tools to achieve educational goals in Indonesia. Most educational institutions in Indonesia are still experiencing some problems in selecting candidates for assistance, because they are still evaluating in a conventional way so that it is feared that the recipients of the assistance will be students or students not fairly and appropriately. target. Therefore, it is necessary to create a Decision Support System for Recipients of Santri or Student Assistance, to determine which students or students fall within the criteria for being eligible to receive such assistance. The criteria used are 6 criteria, namely parents' income, crafts, type of floor of the house, average report card score, parents' occupation, and vehicle ownership. Making this system uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method, which is a decision-making method with a hierarchical structure, which is indeed included in the Multi Criteria Decision Making (MCDM).